Asuhan Keperawatan pada Tn.I dengan Diagnosa Resiko Perilaku Kekerasan di Ruang Lily 15 Soerojo Hospital, Magelang - Amik, Mukhamad Miftah Izul; Apriliyani, Ita (Pusat Riset dan Inovasi Nasional, 2025)
Violent behavior is a form that aims to hurt someone physically or psychologically. Violent behavior can be done verbally, directed at oneself, others, and the environment. Violent behavior towards others is an aggressive act aimed at injuring or killing others. Violent behavior in the environment can be in the form of behavior that destroys the environment, throwing glass, tiles, and everything in the environment. The purpose of this study was to describe nursing care for patients at Risk of Violent Behavior. The sample used was 1 patient. This study was conducted to determine the appropriate nursing care for the risk of violent behavior in patients by implementing the implementation strategy (SP). The results of the study after implementation (SP1-SP4) the problem of the risk of violent behavior was resolved.